20 years of experience with tumour necrosis factor inhibitors: what have we learned?. (5th October 2018) - Caporali, Roberto; Crepaldi, Gloria; Codullo, Veronica; Benaglio, Francesca; Monti, Sara; Todoerti, Monica; Montecucco, Carlomaurizio
Abstract: TNF inhibitors are biologic DMARDs approved for the treatment of active RA in mid-1990s. They still represent a valuable therapeutic option to control the activity, disability and radiographic progression of the disease. In the context of TNF inhibitors, there are currently several molecules and different administration routes that provide optimal treatment personalization, allowing us to respond to a patient's needs in the best possible way. The increasing use of TNF inhibitors has not only improved the management of RA, but it has also helped in our understanding of the pathogenetic mechanisms of the disease. This review focuses on the basis of this targeted therapy and on the knowledge gained from their use about therapeutic effects and adverse events. Effectiveness analysed from drug registries and safety issues are presented together with recent data on infections (in particular, Mycobacterium tuberculosis and hepatitis B), cancer (lymphoma, skin cancers) and cardiovascular risk.